Use of date palm trunk as arid sandy soil amendments for early growth of okra [Abelmoschus esculentus (L.) Moench] - Al-Soufi, Maryam Haroon (2019)
Cultivation in barren soils such as arid soil which covers around 12% of the earth’s surface offers a potential remedy for the alarming global food-shortage. Improving infertile arid soil quality mainly its water holding capacity (WHC) can be done for crop production purposes and agricultural water conservation in arid regions with limited irrigation water resources. One of the common for WHC enhancement is using soil amendments including organic wastes such as biochar and date peat. Therefore, this study uses waste trunk of two major date palm (Phoenix dactylifera L.) cultivars, Khunaizi (KZ) and Khalas (KS) from the eastern region of Saudi Arabia to develop semi-powder form trunk used as organic amendment and mixed with arid soil from the Fodah district to develop and charasteised trunk mixtures used as a medium for the early growth of Abelmoschus esculentus (okra). The experiment was laid out in a randomized complete block design with three replicates. KZ and KS trunks were ground by multistage mill to particle size around 880 μm. Then, chemical (toxicity test, extractable nutrients and pH measurement, high cation exchange capacity, and thermogravimetric analysis), physical (sieve analysis, bulk density, porosity, and water retention), and biological (microbial enumeration) properties of all these samples were determined. Samples of KZ and KS were mixed with sandy soil at four application rates (25, 50, 75, 100 % w/w) and 10 % w/w of organic fertilizer (sheep manure) was added to each mixture. These was followed by cultivating okra seed in these processed mixtures along with individual controls of sandy soil, multi-soil, a commercial growth media, and KS and KZ amendments. During the cultivation stage, the following growth parameters were measured (seed germination duration, root length, plant height, leaf surface area, leaf numbers, assessment of chlorophyll, total soluble sugar, total protein contents, and WHC to assess the efficiency of the early growth of okra in the developed trunk mixtures. KZ and KS at 100% rate resulted in the lowest okra growth rate and higher preparation cost therefore, they are not recommended. Whereas 25% is the optimal amendment rate resulting in optimal fertility characteristics including lower bulk densities of 40% for KZ and 36.6% for KS and higher porosity rates of 45.7% for KZ and 41.2% for KS compared to sandy soil control, higher early growth rate of okra, and the lowest preparation cost. Multi-soil samples showed higher growth rate than KZ and KS for roots density, sugar content, okra height, and leaf surface area that were possibly attributable to higher NPK content. Therefore, higher than 10% w/w of organic fertiliser is recommended to be added to KZ and KS mixtures. Field capacity, permanent wilting point, available water for plant were significantly higher for KZ amendments at 114%, 52%, 62% and for KS 118%, 52%, 65% compared to 7%, 3%, 5% for sandy soil control. Some of study analyses such as available water for plant and most of okra growth parameters such as germination percentage show insignificant results for both KZ and KS. Whereas some other study analyses such pH, and porosity show significant difference between KZ and KS. Although they were cultivars for date palm, they have some non-similar characteristics which may affect their suitability as growth media for okra. This study shows that the four mixtures of KZ and KS showed significant growth rate of okra for root length, sugar content, seed germination, and high WHC (4.7-17.7 %) with 3.6-10% increase on WHC compared to control sandy soil samples and comparable (16 %) to the commercial multi soil media. This can be explained by the natural fibre properties of trunk, elemental composition, morphological structure such as its high hydroxyl groups (OH) content and its hollow tubular structure. Therefore, KZ and KS are recommended as soil amendments and as alternatives to imported expensive commercial growth media due to their low cost, availability and abundance of date-palm cultivation in some Middle East countries such as Saudi Arabia. They can also be used as a sustainable and environment-based solution for combating desertification, water scarcity, and wastes accumulation particularly in arid regions by improving arid soil low productivity and fertility mainly WHC. Finally, it is recommended to extend this study for the cultivation of a wide range of the same plant family.